1986
DOI: 10.3354/meps033099
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and trophic coupling in pelagic microorganisms in eutrophic coastal waters

Abstract: Pelagic bacteria, heterotrophic and autotrophic nanoflagellates, and ciliates were quantified in the marine shallow-water sound, Limfjorden, Denmark, from March to November 1983. During summer the populations showed pronounced oscillations with time scales of days or weeks. Concentrations of bacteria, heterotrophic nanoflagellates and ciliates ranged from 0.5 to 15.2 X 106 ml" (mean: 6.3), 0.2 to 15.2 X 103 ml-' (mean: 2.0), and 1.4 to 162.0 ml-' (mean: 17.1), respectively. Population sizes of bacteria and het… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
35
0
8

Year Published

1988
1988
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 15 publications
10
35
0
8
Order By: Relevance
“…To examine this possibility, specific clearance rates were calculated by dividing grazing rates by bacterial densities (Table 4). Results showed that specific clearance rates of HNF in Uranouchi-Wan were 1 to 3 nl HNF -1 h -1 and those were exactly similar range to those previously reported (Andersen and Sørensen, 1986;Fukami et al, 1991a) but that HNF clearance rates in the 5 and 10 m depths were generally higher than those in surface layer (Table 4). This suggests that HNF in deeper layers were more active than the surface ones.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…To examine this possibility, specific clearance rates were calculated by dividing grazing rates by bacterial densities (Table 4). Results showed that specific clearance rates of HNF in Uranouchi-Wan were 1 to 3 nl HNF -1 h -1 and those were exactly similar range to those previously reported (Andersen and Sørensen, 1986;Fukami et al, 1991a) but that HNF clearance rates in the 5 and 10 m depths were generally higher than those in surface layer (Table 4). This suggests that HNF in deeper layers were more active than the surface ones.…”
Section: Discussionsupporting
confidence: 76%
“…From many recent studies, it is generally accepted that HNF is one of the most important bacterial consumers (Andersen and Sørensen, 1986;Fenchel, 1986;Rassoulzadegan and Seldon, 1986;Pace, 1988;Wikner and Hagström, 1988;Nakamura et al, 1994). Previous studies have clarified the distribution of bacteria and HNF in various aquatic environments.…”
Section: Introductionmentioning
confidence: 99%
“…Our values for flagellate abundances were close to those obtained in the St. Lawrence estuary, 1.9 X 106 to 6 X 106 cells 1-' (Lovejoy et al 1993), and in the marine shallow-water Lirnfjorden in Denmark, 2 X 106 cells 1-' (Andersen & Sarensen 1986).…”
Section: 126038supporting
confidence: 62%
“…In marine pelagic environments, heterotrophic nanoflagellates are the most probable consumers of bacterial cell production (Fenchel 1984(Fenchel , 1986. Laboratory experiments with cultured flagellates have demonstrated that they are adapted to predation on bacteria-sized particles (Fenchel 1982a), and they occur in seawater in concentrations sufficient to control bacterial biomass (see Sherr and Sherr 1984).…”
mentioning
confidence: 99%